Arabic translation, cultural adaptation, and validation of Australian Pelvic Floor Questionnaire in a Saudi population - Haifaa Malaekah; Haifaa Saud Al Medbel; Sameerah Al Mowallad; Zahra Al Asiri; Alhanouf Albadrani; Hussam Abdullah (BMC, 2021)
Abstract Introduction and hypothesis The aims of the study were the translation, cultural adaptation, and validation of self-administered Australian Pelvic Floor Questionnaire (APFQ) on a Saudi population. Methods The translation and cultural adaptation was performed in 854 women over 18 and not pregnant who agreed to answer the Arabic version of the questionnaire. The content/face validity, internal consistency (reliability), and construct validity (factor analysis) were assessed. Statistical analysis was carried out using SPSS 24.0 statistical software. Results The Cronbach's alpha results were above 0.8 for the questionnaire's overall reliability (bladder function: 0.877, bowel function: 0.834, prolapse symptoms: 0.784, sexual function: 0.762) showing adequate internal consistency reliability and high statistical significance. A statistically significant correlation was observed among the 40 items of the questionnaire. The issue of multicollinearity was not found, and the determinant of the correlation matrix was 0.001. A value of > 0.5 was achieved when the Kaiser-Meyer-Olkin and Bartlett's tests measured 0.806 and the Bartlett's test of sphericity was statistically significant χ2 (780) = 4150.46 (p < 0.001). The values of loading indicate that all 4 factors (bladder function, bowel function, prolapse symptoms, sexual function) contributed to each of their items. Conclusions This study provides the Arabic version of the self-administered APFQ as a reliable and valid instrument for evaluating symptom severity and impact of pelvic floor dysfunction on the quality of life of Arabic women. It also will enable the researchers from Arab countries to use this instrument to assess pelvic floor dysfunction prevalence in their settings.